The importance of eco-labels certifications and ICT in the promotion of sustainable tourism - Lúcia Pato (Instituto Politécnico de Viseu, 2020)
Introduction: In an era of increasing environmental problems, the sustainable conduct of tourism enterprises, particularly in rural tourism, is now of central importance. A good part of the market tends to look for an environmentally friendly and socially responsible enterprise. Hence, information and communication technologies (ICT) are fundamental for the transmission of these principles.  Indeed, not only promoters but also e-commerce companies in the field of travel are aware of this reality and need, trying to skillfully communicate their respective sustainable tourism offer.  A notable example that highlights the importance of environmental and social sustainability and the value of using information and communication technologies (ICT) is located in the Viseu Dão-Lafões Region (RVDL), more precisely in one of the most interior communities of the region.  Objetives: Taking as a unit of analysis a rural tourism enterprise in VDLR, the purpose of this study is to explore the importance of sustainability strategies and ICT for delivery and promotion of the touristic product.  Methods: In order to allow a deeper analysis, a case study methodology is used. In addition to a semi-structured interview with the entrepreneur of the unit, it was observed and analyzed the web page of the unit and other electronic documents.  Results: In the genesis and development of this enterprise there was always a concern with the environment and with the community. Hence, the enterprise is in a process of certification by Biosphere and Green Key. Whether it is in the development and updating of the web page, social networks, response to evaluations on TripAdvisor / Booking and updating channels of disclosure when reservations are made, the promotion / communication of the most sustainable tourism offer through ICT, occupies the majority of the time that the promoter dedicates to the enterprise.  Conclusions: The existence of an environmental conduct by the rural tourism enterprise, and the communication of this conduct, is assumed as a fundamental ingredient for the success of the tourist activity of the enterprise. Moreover, it is fundamental for the attraction of a new tourist more concerned with environmental issues.